Environmentally sustainable tourism development in mountain regions: A systematic literature review - Yusrizal Adytia Firdaus (Institute of Advance Science, Social, and Sustainable Future, 2026)
Background: This study was designed to integrate previous research findings and focus on comprehensive considerations regarding sustainable tourism development in ecologically vulnerable areas such as mountain peaks in Indonesia. This study aims to analyze and synthesize the development of sustainable tourism in Indonesia by reviewing thirteen key academic studies selected from thousands of publications based on inclusion and exclusion criteria. This research is significant from an academic perspective and is aimed at contributing to the development of literature on sustainable tourism by discussing the specific context of the mountainous region in Indonesia. Methods: This research uses the SLR or Systematic Literature Review method to provide a comprehensive review of how the tourism business affects the environment and to find an overview of the concept of sustainable tourism that is more environmentally friendly. The steps of the SLR method are described in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol framework guidelines. Findings: Based on a comparative analysis of thirteen reviewed studies, this research proposes a conceptual framework for Environmentally Friendly and Improved Sustainable Tourism (EFIST) Indonesia's mountainous regions. This conceptual model highlights that the future of sustainable mountain tourism in Indonesia depends on how effectively these four elements—ecology, community, technology, and governance—are synchronized. Conclusion: The synthesis of this systematic literature review analysis culminates in the EFIST conceptual framework, which positions sustainable tourism in mountain areas as an integrated system, rather than a segmented practice. Novelty/Originality of this article: This study offers the EFIST model as a framework for policymakers, researchers, and practitioners to implement more cohesive and future-oriented tourism strategies in Indonesia and around the world.